Resolution Forum of Syariah Ekonomy Dispute - Zaenah (Hang Tuah Law Journal, 2018)
Both No. 93/PUU-X/2012 and PERMA No. 14 Year 2016 regulate a forum of resolution for syari’ah economy disputes, particularly the dispute that arises in a contractual relationship between syari’ah banks and their customers, whether in litigation or nonlitigation setting. The development of syari’ah banking is still far due to the pressure of globally financial and economy crisis. Therefore, it is the best moment to pursue the development and progress of syari’ah banking by exhibiting the advantages of Islamic economy system that has competence to compete with the convensional ones, especially in terms of customer security assurance in the process of seeking for business dispute resolution which may possibly happen. Such process, however, remains in syari’ah corridor with kaffah and istiqomah attributes. For people in syari’ah business, all the transactions they do should be under the provisions of syari’ah regulation. An appropriate forum to seek for syari’ah economy dispute resolution is through mediation, given that it is the best one and more reflecting the values of Islam.